2011
DOI: 10.1213/ane.0b013e3182315a6d
|View full text |Cite
|
Sign up to set email alerts
|

Operation Timing and 30-Day Mortality After Elective General Surgery

Abstract: Elective general surgery appears to be comparably safe at any time of the workday, any day of the workweek, and in any month of the year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…(1012) In contrast, Sessler found no correlation between a composite complication score after general surgery and case start time by using the United States Agency for Healthcare Research and Quality’s Clinical Classifications Software (AHRQ-CCS). (13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1012) In contrast, Sessler found no correlation between a composite complication score after general surgery and case start time by using the United States Agency for Healthcare Research and Quality’s Clinical Classifications Software (AHRQ-CCS). (13…”
Section: Discussionmentioning
confidence: 99%
“…(14) No difference in mortality was found in an academic setting having non-emergent surgery with evening start times when controlling for patient factors. (13, 15) Transplant patients having evening surgery have the same mortality to those performed during daytime hours. (12, 16)…”
Section: Discussionmentioning
confidence: 99%
“…A single-center study analyzing 32,001 elective general surgical patients showed a trend toward increasing mortality and complications as the day progressed from 6 am to 6 pm; however, these differences were not significant. 15 Results from studies on cardiac surgery and orthopedic surgery showed comparable outcomes between surgeries performed during the day and during the night. 13,16 Trauma surgery, however, is unique in that it is always emergent and is performed at all times of the day.…”
Section: Commentsmentioning
confidence: 97%
“…They could not demonstrate any differences between weekday, time of day or different months concerning 30-day mortality, concluding that surgery was safe on any day and any time of the week [21].…”
Section: Week Day Percentagementioning
confidence: 90%